Evaluasi Program Proyek Penguatan Profil Pelajar Pancasila (P5) Menggunakan model Goal Free di SD GMIT Tepas - Martince Benu; Wasitohadi; Sophia Tri Satyawati (Universitas Kristen Satya Wacana, 2026)
This study evaluates the implementation of the Pancasila Student Profile Strengthening Program (P5) at GMIT Tepas Elementary School, focusing on its planning, implementation, challenges, and impact. Using a qualitative approach, the study collected data through in-depth interviews, observations, focus group discussions (FDGs), and documentation, with data analysis using the Creswell model. The P5 planning proved successful in generating positive impacts, particularly in building initial understanding and support from students, parents, and the school community through effective outreach. The planning also established a systematic program implementation structure, including the formation of a facilitator team, scheduling, and the development of project modules. Furthermore, the planning facilitated the identification of student learning needs through diagnostic assessments, which is crucial for determining relevant project themes. These efforts provide a strong foundation for holistic character development. In terms of implementation, P5 successfully increased student engagement and teacher competency. However, the program faced significant challenges from both internal (e.g., lack of teacher training and limited resources) and external (e.g., limited parental support) factors. Thanks to effective coordination between the principal and teachers, these obstacles were overcome. The impact of P5 is very strong on students' character and Pancasila values. This program successfully increases moral awareness, empathy, tolerance, critical thinking, independence, and social skills. The results of the study, which included a Goal Free evaluation, showed that the implementation of P5 had a positive impact, as evidenced by a 10.6% increase in character indicators in the school quality report. This confirms P5 contribution to improving the quality of education at the school.